An Entrepreneur’s Personal Value Perspective in Managing Product Harm Crises - Erandi Wattegama; Qing Ping (International Journal of Management, Accounting and Economics, 2015)
Product harm crises often reflect the outcomes of firms’ unethical business decision-making behaviours. Literature showed that the majority of crisis management studies have paid high attention for finding strategies from the consumer’s perspective. Hence, the purpose of present study is set to conceptualise the impact of an entrepreneur’s personal values on making ethical business decisions to fill the empirical gap that has been arisen from a firm’s perspective. A systematic approach was followed to review the crisis management literature and to examine the current status of product harm crisis management strategies in scholarly accepted databases. The analyzed content found that the relationship among the variables of entrepreneur’s personal values, firm’s attitude towards fulfilling the corporate social responsibilities, and the ethical decision-making behaviour can be explained through the value- attitude-behaviour hierarchy model. Some propositions have been suggested as future research directions for academia and it is believed that the present study finding is a pre-requisite for the content provision from a firm’s perspective in product harm crisis management study context.